Exercise motives among university students – A Brazil-Portugal transnational study - Campos, Lucas Arrais; dos Santos, Adrielly; Sampaio, Mafalda Margarida Basto; Marôco, João; Campos, Juliana Alvares Duarte Bonini (Frontiers in Psychology, 2022)
Background: Identifying the motives why people exercise is interesting for the planning of effective health promoting strategies. Objectives: to estimate the psychometric properties of the Exercise Motivations Inventory (EMI-2) in Brazilian and Portuguese university students, and to compare motive-related factors for exercise among students. Methods: One thousand Brazilian (randomly splitted into “Test sample” [n=498] and “Validation sample” [n=502]) and 319 Portuguese students participated in this cross-sectional study. Motives for exercise were evaluated using EMI-2. Exploratory factor analysis (EFA) was performed in the Test sample. Then, confirmatory factor analysis was performed in the Validation and Portuguese samples. The EMI-2 scores were compared according to sex, exercise, and weight status (ANOVA, α=5%). Result: EMI-2 factor model was explained by 5 factors and presented adequate fit (2/df≤3.2; CFI≥0.9; TLI≥0.9; RMSEA≤0.07; and α≥0.83). The motives for exercising were mainly related to psychological and interpersonal factors for men, health-related factors for women, and body-related factors for overweight and obese individuals. People who practice exercise had higher EMI-2 scores. Conclusion: The 5-factor model is suggested for a comprehensive assessment of motives for exercise. Individual characteristics should be considered for development of tailored protocols.